Effector gene prediction from fungal pathogen genome assemblies - Testa, Alison Clare (Curtin University, 2016)
Fungal phytopathogens interact with their hosts largely via the secretion of effectors, which manipulate and elicit plant defences. This research contributes to the discovery of effectors from fungal pathogen genome assemblies through improved fungal gene predictiontechniques, an investigation into AT-rich genome regions, relevant to the genomic context of effectors, and improved genomic resources and effector candidate lists for barley pathogens Pyrenophora teres f. teres and Pyrenophora teres f. maculata.